2012
DOI: 10.1090/conm/561/11114
|View full text |Cite
|
Sign up to set email alerts
|

On the spectra of algebras of analytic functions

Abstract: Abstract. In this paper we survey the most relevant recent developments on the research of the spectra of algebras of analytic functions. We concentrate mainly in three algebras, the Banach algebra H ∞ (B) of all bounded holomorphic functions on the unit ball B of a complex Banach space X, the Banach algebra of the ball Au(B), and the Fréchet algebra H b (X) of all entire functions bounded on bounded sets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The purpose of this note is to exhibit that the Cluster Value Theorem holds for every Banach space X whose dual has the bounded approximation property for the algebras A u (B X ), H b (X) and to several open problems in the area (in particular, it gives answers to the questions posed in [17,Remark 2.5] and also [11,Questions 7 and 8]).…”
mentioning
confidence: 99%
“…The purpose of this note is to exhibit that the Cluster Value Theorem holds for every Banach space X whose dual has the bounded approximation property for the algebras A u (B X ), H b (X) and to several open problems in the area (in particular, it gives answers to the questions posed in [17,Remark 2.5] and also [11,Questions 7 and 8]).…”
mentioning
confidence: 99%
“…The first steps towards the description of the spectrum of H b (X) were taken by Aron, Cole and Gamelin in [6]. A survey with the most relevant recent developments on the research of the spectra of algebras of analytic functions can be found in [54]. We also show, as in the case of H b (X) and HW (X), that any function f ∈ V H(X) extends naturally to an analytic function defined on the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to [8,11] for general theory on complex analysis in Banach spaces, and to [5,6,8,10,13] for background on the space of holomorphic functions of bounded type and its spectrum.…”
Section: Introductionmentioning
confidence: 99%